Peningkatan Minat Baca Siswa Melalui Pekan Literasi dan Pembiasaan 15 Menit Membaca: Studi Kasus MI Mulyadarama Girimukti - Prayoga, Reka Ardi; Budiarto, Hanif Azis; Afif, Muhammad Fadhlan; Pradipta, Adi Surya; Lestari, Adinda Sri (Warta LPM, 2023)
The School Literacy Movement (GLS) has been implemented since March 2016. However, its implementation is still not effective in West Java. This study aims to increase reading interest in MI Mulyadarma, Girimukti Village, Cipongkor District, West Bandung Regency. This school has limited internet access, book diversity, and school facilities, that are below the standards of an ideal school. Student’s interest in reading is increased in two ways. The first way is by encouraging 4th-6th grade elementary school students to read for 15 minutes before the class starts, for 3 weeks. The second way is by providing mini libraries in each classroom. Data collection was done using questionnaires. The questionnaire was given before and after the program, so that the achievement of the program could be evaluated. The result shows that the reading habit for 15 minutes before class and providing mini libraries in the classroom successfully increased students’ interest in reading significantly. Students who read books for more than 60 minutes per day increased by 33%. Student interest in reading increased by 64%, while their reading awareness increased slightly by 12.5%.